Efficient liquid exfoliation of KP15 nanowires aided by Hansen's empirical theory - Huang, Zhaoxuan; Jiang, Zhikang; Tian, Nan; Yao, Disheng; Long, Fei; Yang, Yanhan; Liu, Danmin (Beilstein Journal of Nanotechnology, 2022)
The KP15 nanowires with one-dimensional properties has a defect-free surface, high anisotropy, and carrier mobility which is desirable for the development of novel nanodevices. However, the preparation of nanoscale KP15 is still inefficient. In this work, the Hansen solubility parameters of KP15 were first obtained. Based on the Hansen's empirical theory, the concentration of liquid-exfoliated KP15 nanowires was improved to 0.0458 mg·mL−1 by a solution containing 50% water and 50% acetone. Approximately 79% of the KP15 nanowires had a thickness value below 50 nm and 60.9% of them had a width value below 100 nm. The thinnest KP15 nanowires reached 5.1 nm and had smooth boundaries. Meanwhile, strong temperature-dependent Raman response in exfoliated KP15 nanowires has been observed, which indicates a strong phonon–phonon coupling in those nanowires. This is helpful for non-invasive temperature measurements of KP15 nanodevices.
Keywords: Hansen's empirical theory; KP15; liquid exfoliation; nanodevices; nanowires; Raman; semiconductors